A comparative study of maternal and fetal outcome in trial of labour after caesarean delivery and elective repeat caesarean delivery - Neravi, Asha; Kulkarni, Namrata; Brindhini, M. Usha; Udayashree, V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Globally, high rates of caesarean section (CS) are an issue of public health concern. For women who have had a previous caesarean, choices for mode of birth in their next pregnancy are either a trial of vaginal birth after caesarean (TOLAC) or an elective repeat caesarean delivery (ERCD). Both ERCD and TOLAC have benefits and risks associated. Methods: A prospective comparative study was conducted in the Department of Obstetrics and Gynecology at SDM college of medical science and hospital, Dharwad, Karnataka, India. The study included 80 women with one previous lower segment caesarean section over a period of 1 year. A 40 women underwent TOLAC and 40 women had a repeat caesarean section. The maternal and fetal outcomes in trial of labour after caesarean delivery and repeat caesarean delivery were compared. Results: In this study maternal morbidity was more common in ERCD group than in the TOLAC group. Neonatal outcome was the same in both the study groups. Conclusions: In our study the TOLAC success rate was 70-80%, pregnant woman with one previous lower segment Caesarean section should be given the option of TOLAC, unless contraindicated.